2008
DOI: 10.1248/cpb.56.1126
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Activities of 4-Phenyl-5-pyridyl-1,3-thiazole Derivatives as Selective Adenosine A3 Antagonists

Abstract: Adenosine, an endogenous purine nucleoside, modulates a variety of physiological functions in various organs and tissues, and interacts with four specific G-protein-coupled receptor subtypes (GPCRs), classified as A 1 , A 2A , A 2B , and A 3 .1,2) All four receptors are coupled via G proteins to the adenylate cyclase-cAMP signal transduction pathway. Activation of A 1 and A 3 receptors inhibits adenylate cyclase through G i coupling, while activation of A 2A and A 2B receptors stimulates adenylate cyclase thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
20
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 33 publications
1
20
0
1
Order By: Relevance
“…Of the 18 non-ring fused thiazole variants, our assay identified five as hits (Figure S4A). However, modeling studies performed to-date suggest that the key receptor-ligand interactions are achieved through the substituents present on the heterocyclic ring rather the thiadiazole itself (Miwatashi et al., 2008). One could therefore envisage that with such simple fragments, binding via alternative geometries is entirely probable and it was encouraging that the more highly decorated heteroaryl-aryl linked hit fragments did indeed possess the superior binding affinities; possible by virtue of additional points of contact with the receptor binding site.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 18 non-ring fused thiazole variants, our assay identified five as hits (Figure S4A). However, modeling studies performed to-date suggest that the key receptor-ligand interactions are achieved through the substituents present on the heterocyclic ring rather the thiadiazole itself (Miwatashi et al., 2008). One could therefore envisage that with such simple fragments, binding via alternative geometries is entirely probable and it was encouraging that the more highly decorated heteroaryl-aryl linked hit fragments did indeed possess the superior binding affinities; possible by virtue of additional points of contact with the receptor binding site.…”
Section: Discussionmentioning
confidence: 99%
“…MRS 1220 N-(9-chloro-2-furan-2-yl- [1,2,4]triazolo [1,5-c]quinazolin-5-yl)-2-phenylacetamide NECA (2S,3S,4R,5R)-5-(6-aminopurin-9-yl)-N-ethyl-3,4-dihydroxyoxolane- The adenosine A 3 receptor (A 3 R), belongs to a family of four adenosine receptor (AR) subtypes (A 1 R, A 2A R, A 2B R and A 3 R), and is involved in a range of pathologies including cardiovascular, neurological and tumour-related diseases. Unsurprisingly therefore, A 3 R is a pharmaceutical target.…”
mentioning
confidence: 99%
“…Interestingly, the A 3 R has been described as enigmatic, whereby many of the effects attributed to A 3 Rs are contradictory 1 . Despite this, A 3 R antagonists having been described as potential treatments of asthma, chronic obstructive pulmonary disease (COPD) and glaucoma 2,3 , continuous research into antagonists at the A 3 R are warranted. It has also been suggested that the A 3 R is over expressed in various tumour cells suggesting it may be a viable drug target against cancer proliferation [4][5][6] .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Заметим, что селек-тивные антагонисты рецепторов А3 аденозина исследуются как потенци-альные противовоспалительные сред-ства [20]. Эти выводы, следующие из результатов хемореактомного анали-за, подтверждаются установленным противовоспалительным действием этифоксина при экспериментальном аутоиммунном энцефалите [21] и на модели отека мозга [22].…”
Section: этифоксинunclassified